Enhancement of Public Awareness of Legal Language through Community Legal Education Program - I Made Dwika Hadinata (Community Service Journal of Law, 2023)
This article discusses community engagement with the title "Improving Public Awareness of Legal Language through Community Legal Education Programs." The aim of this research is to enhance public awareness of legal language through the community legal education approach. The method employed in the execution of the activities involves organizing community legal education programs that actively involve the participation of the community in the learning process. This program is designed to provide fundamental knowledge about legal language, including the understanding and use of legal terms frequently employed in legal contexts. The results of the activity implementation demonstrate an increase in public awareness of legal language. The community becomes more knowledgeable and capable of using legal language accurately and effectively in everyday communication. They are also able to comprehend their rights and responsibilities as citizens, as well as enhance their participation in legal processes. In conclusion, community legal education programs play a crucial role in heightening public awareness of legal language. This program establishes a strong foundation for the community to comprehend and use legal language correctly. Consequently, the community becomes more legally conscious and empowered to safeguard their rights. In the long term, this program holds the potential to cultivate a more engaged community in legal processes and to provide them with a better understanding of their rights and responsibilities.